Peran Keluarga dan Masyarakat dalam Perawatan Pasien Gangguan Jiwa - Tutut Pujianto; Retno Ardanari Agustin (Journal of Ners and Midwifery, 2017)
Mental health is an integral part of health, and a condition that affects the physical, mental, and  social  development  of  the  individual  optimally.  Mental  disorder  is  disturbances  in:  cognitive, volition, emotion (affective), and actions (psychomotor). Mental disorder is a collection of abnormal circumstances, whether physically related, or mentally. It is divided into two groups, namely: mental disorder  (neurosis)  and  mental  illness  (psychosis).  Mental  disorder  is  caused  by  some  of  the  above causes affected simultaneously or coincidence occurs. The purpose of this study was to increase the role of family and society in the treatment of mental disorder patients which was consequently could reduce the number of mental disorders patients This research used obsevational design with descriptive analy- sis. The subjects were family members who treat mental disorder patients as much as 16 respondents. The data collection was done in October 2012. The family role data grouped into appropriate and inappro- priate  category.  The  research  found  that  11  people  (68.75%)  in  the  category  of  inappropriate,  and appropriate by 5 people (31.25%), with average family role of 63.19%. The higher of inappropriate category was because 9 respondents (56.25%) in the age of elderly (> 50 years). This condition caused a decrease in the ability to perform daily activities, including health treatment. There were 4 patients who have been treated for 7-14 years, so the family feels accustomed to the condition of the patient. There were 8 people (50%) in productive age treated the patients, so it could not be done continuously. Based on these conditions, there should be efforts to increase knowledge and willingness of the patients and families, in caring for patients with mental disorders. The examples of such activities were to consult with the nearest health employees, and report to the health worker if there is a risky condition immedi- ately.